2011
DOI: 10.1007/s00246-011-9909-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Brain Natriuretic Peptide Concentrations to Left Ventricular Function and Adverse Outcomes in Children With End-Stage Renal Disease Undergoing Hemodialysis

Abstract: B-type natriuretic peptide (BNP) is a biomarker of cardiovascular disease that is common in adults with chronic kidney disease (CKD). However, in children with CKD, the range and predictive power of BNP concentrations are not known. We aimed to determine the effect of HD on BNP, as well as the prognostic impact of BNP, in end-stage renal disease (ESRD) children undergoing hemodialysis (HD). Thirty-five children with chronic renal failure (16 boys age 12.1 ± 3.7 years) on maintenance HD were included. BNP level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…Kumar et al [40] measured NT-proBNP in 366 stable outpatients undergoing hemodialysis with a corresponding pre-and post-dialysis multifrequency bioimpedance assessment of extracellular water and they reported that serial NT-proBNP values may aid clinical assessments of volume status in patients undergoing dialysis. Ouali et al [41] identified a significant correlation between BNP concentrations and left ventricle functions in patients with CKD undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al [40] measured NT-proBNP in 366 stable outpatients undergoing hemodialysis with a corresponding pre-and post-dialysis multifrequency bioimpedance assessment of extracellular water and they reported that serial NT-proBNP values may aid clinical assessments of volume status in patients undergoing dialysis. Ouali et al [41] identified a significant correlation between BNP concentrations and left ventricle functions in patients with CKD undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…High plasma BNP levels were reported as a risk factor for cardiovascular morbidity and mortality in children with end-stage renal disease undergoing hemodialysis. Significant correlation was detected between BNP concentrations and left ventricle functions from Ouali et al 25 . Liu and colleagues were determined as BNP cut-off value as 353 pg/mL in adults undergoing hemodialysis with normal EF value 26 .…”
Section: Echocardiography Resultsmentioning
confidence: 83%
“…There are conflicting reports about the value of BNP as a biomarker of volume status in CKD patients. Some reports showed that BNP did not change significantly after the reduction of body weight in children on HD, but in others, BNP decreased significantly after HD . The reduction of BNP was interpreted as a reduction of plasma volume and relief of hypervolaemia after HD .…”
Section: Discussionmentioning
confidence: 99%